Gait analysis following release of the short external rotators during an anterior approach for total hip arthroplasty. Issue 6 (November 2018) - Petis, Stephen M; Vasarhelyi, Edward M; Howard, James L; Lanting, Brent A
Background: Cadaveric and clinical studies suggest surgical release of the short external rotators is sometimes necessary to improve exposure during total hip arthroplasty (THA) using an anterior approach. The purpose of this study was to determine the impact of those surgical releases on gait following THA. Methods: 15 patients undergoing THA using an anterior approach, anterior approach with surgical releases, or posterior approach underwent 3-D gait analysis preoperatively, and at 6 and 12 weeks postoperatively. At each time point, temporal parameters, kinematics, and kinetics were compared. The anterior approach was compared to the anterior approach cohort with surgical releases, and the surgical release cohort was compared to a posterior approach cohort. The mean change score between preoperative and 6 weeks, and 6-week to 12-week analyses were analysed. Results: There were no demographic differences between the groups. There were no significant differences between the groups for the temporal parameters and kinematic analyses at either time point comparison. The surgical release cohort had a lower hip internal rotation moment compared to the anterior approach cohort for the 6- to 12-week comparison ( p = 0.05), and compared to the posterior approach cohort for the preoperative to 6-week ( p = 0.03) and 6- to 12-week comparison ( p = 0.02). Conclusion: Releasing the short external rotators during an anterior approach did not cause significant temporal and kinematic changes after THA. However, small changes in hip internal rotation moments can be expected. These findings should be correlated with patient-reported outcome measures to determine if these gait anomalies predict poor outcome following THA.